Penerapan Kegiatan Bermain Peran untuk Meningkatkan Kemampuan Sosial Emosional pada Anak Usia Dini di PAUD Terpadu Kartini Madu Mawar - Sri Yeni Puspitasari; Diana Diana; Iin Maulina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aimed to ascertain and describe the implementation of role-playing activities to enhance the socio-emotional skills of early childhood at PAUD Terpadu Kartini Madu Mawar. This research employed a descriptive method with a qualitative research approach and Classroom Action Research (CAR). The subjects of this study were children aged 4-5 years in Group B and their class teacher at the PAUD. Data collection techniques included observation, interviews, and documentation. Data analysis was performed using descriptive percentages. There was a noticeable increase in children's knowledge and skills before and after the implementation of role-playing activities to foster socio-emotional skills at PAUD Terpadu Kartini Madu Mawar, as evidenced by the observation sheets. This finding was derived from data analysis using the descriptive percentage formula. The learning outcomes depicted in Cycle III showed 46.25% in